Migrant Remittances as a Mechanism of Social Protection: Evidence from South and East Asia - Neupane, Bishnu Prasad; Bhandari, Tikaram (Archives of Business Research, 2025)
Migration has emerged as a defining feature of the socio-economic landscape in South and East Asia, with millions of individuals moving across borders in search of better livelihoods. The remittances sent by these migrant`s financial transfers to their families and communities back home have grown to become a critical source of income for many households in the region and stands as a social protection mechanism. In 2024, South and East Asia collectively received over 250 billion in remittances, accounting for a significant share of global remittance flows and often surpassing official development assistance and foreign direct investment in several countries (World Bank, 2024). Remittances significantly enhance household income in recipient countries, acting as informal social protection by supporting families during economic shocks, health crises, and unemployment, particularly where formal systems are weak, such as for marginalized and rural groups (Rahman & Yeoh, 2023). Their importance grew during global crises like COVID-19, which highlighted gaps in state-led social protection (ADB, 2023). Remittance flows are influenced by migration policies, labor markets, gender norms, and digital financial services, with diverse patterns across South and East Asia, from large-scale labor migration in the Philippines, Bangladesh, and Indonesia to intra-regional movements in China and Vietnam (IOM, 2024). Digitalization has improved the accessibility and efficiency of these transfers.